MPEG compression and client user interface for a surveillance system - 223269 Lee, Vincent Wei Han (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Electrical (Computer Engineering)) - Universiti Teknologi Malaysia, 2003